KAJIAN POTENSI PEMANFAATAN SAMPAH PLASTIK MENJADI BAHAN BAKAR CAIR - Sari, Gina Lova (Al-Ard: Jurnal Teknik Lingkungan, 2017)
The abundance of plastic waste is caused by inadequate management. The element of plastic waste consists of crude oil and natural gas that can be reuse as fuel. The conversion technique which can be applied is thermal cracking as known as pyrolysis that combined with a catalyst. The addition of a catalyst can accelerate the process of crude oil formation so that the volume increases and makes the quality better. The pyrolysis can convert waste into oil up to 81% that are consist of paraffin, isopropyl, olefin, naphthal and aromatics so feasible to use as fuel. Keywords: catalyst, crude oil, fuel, plastic waste, pyrolysis.